Muslim Albania: Kisah Islam Marginal - Herdi Sahrasad (Budapest International Research and Critics University, 2017)
According to Albanian Muslim intellectual Ervin Hatibi, Albanian Muslims are not monolithic and have their own secularist traditions, so it is not only Christians who have the phenomenon of secularism like Bernard Lewis's view. Least. Albania as a small country with three Abrahamic / religious beliefs: Islam, Orthodox Christianity and Catholicism, have the opportunity to compete in virtue, where Muslims return to find their mosque, and Christians / Catholics return to find their church. The road ahead has implied a tuft hope.